2019
DOI: 10.1172/jci127483
|View full text |Cite
|
Sign up to set email alerts
|

Selective DNA-PKcs inhibition extends the therapeutic index of localized radiotherapy and chemotherapy

Abstract: Potentiating radiotherapy and chemotherapy by inhibiting DNA damage repair is proposed as a therapeutic strategy to improve outcomes for patients with solid tumors. However, this approach risks enhancing normal tissue toxicity as much as tumor toxicity, thereby limiting its translational impact. Using NU5455, a newly identified highly selective oral inhibitor of DNA-dependent protein kinase catalytic subunit (DNA-PKcs) activity, we found that it was indeed possible to preferentially augment the effect of targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 53 publications
(55 reference statements)
1
44
0
Order By: Relevance
“…Additionally, DNA-PK has an RNA-dependent, cNHEJ-independent function during ribosome biogenesis that requires kinase activity of DNA-PKcs [ 37 ]. Based on these features, DNA-PKcs often protects tumor cells from DNA damage that derives from chemotherapy and radiotherapy [ 38 41 ]. Specifically, DNA-PKcs promotes proliferation, inhibits apoptosis and facilitates DNA-repair of HCC cells independent of p53 [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, DNA-PK has an RNA-dependent, cNHEJ-independent function during ribosome biogenesis that requires kinase activity of DNA-PKcs [ 37 ]. Based on these features, DNA-PKcs often protects tumor cells from DNA damage that derives from chemotherapy and radiotherapy [ 38 41 ]. Specifically, DNA-PKcs promotes proliferation, inhibits apoptosis and facilitates DNA-repair of HCC cells independent of p53 [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of DNA-PKcs is frequent in a variety of cancer types and predicts poor prognosis in patients [ 9 , 10 , 11 , 12 , 13 , 14 ]. Consequently, DNA-PKcs has been shown to be a potential therapeutic target, especially in combination with radio- and chemotherapy that induce DNA damage [ 2 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, it is not clear whether transient pharmacological inhibition of DNA-PKcs can be applied jointly with radiation without increasing toxicity at the same time. Willoughby et al [ 103 ] reported the identification of NU5455, a novel highly selective orally bioavailable inhibitor of DNA-PKcs activity. NU5455 was used to evaluate pharmacological DNA-PKcs inhibition in combination with RT in a cell line panel, including HCC cell lines, by examining the responses of both tumor and normal tissues to treatment.…”
Section: Radiosensitization Strategiesmentioning
confidence: 99%